Nuclear accents in four Irish (Gaelic) dialects - NI CHASAIDE, AILBHE (My University, 2007)
In this paper the distribution of nuclear accents in declaratives of four major dialects of Irish is described. The findings show considerable variation, particular between northern and southern dialects. Speakers of the northern dialect of Donegal show a propensity for rising nuclear accents (L*+H) in declaratives, while speakers of the other, more southern, dialects of Mayo, South Connaught and Kerry Irish show a preference for falling nuclear (H*+L) accents. The findings are compared with results for varieties of English.
Proceedings of the XVIth International Congress of Phonetic Sciences
PUBLISHED
Keywords: Irish language